2019
DOI: 10.24042/atjpi.v10i1.3631
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Problem Based Learning Untuk Menangkal Radikalisme Pada Peserta Didik Sma Negeri Di Kota Bandar Lampung

Abstract: Through the development of Islamic religious education teaching materials based on problem based learning, it is expected to further enhance the knowledge of Islamic religion of students, so that it is easier for these students to ward off radicalism. The purpose of this study (i) how is the development of Islamic religious education teaching materials based on problem based learning to counteract radicalism in students? (2) how is the effectiveness of Islamic religious education teaching materials based on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
1
7
0
7
Order By: Relevance
“…Kelebihan dari penggunaan model pembelajaran yaitu membantu siswa dalam mengembangkan kemampuan berpikir kritis dalam pemecahan masalah, kreatif, dan berkomunikasi kolaborasi kegiatan belajar kelompok (Nurhayati dkk, 2019;Syafei, 2019;Selviani, 2019). Dalam penerapan model pembelajaran Problem Based Instruction pada mata pelajaran IPS materi kelangkaan dan kebutuhan manusia guru bisa mensimulasikan permasalahan kelangkaan sumber daya yang terbatas dihadapkan dengan kebutuhan manusia yang tidak terbatas sebagai konteks bagi siswa untuk mempelajari materi tersebut.…”
Section: Problem Based Instructionunclassified
“…Kelebihan dari penggunaan model pembelajaran yaitu membantu siswa dalam mengembangkan kemampuan berpikir kritis dalam pemecahan masalah, kreatif, dan berkomunikasi kolaborasi kegiatan belajar kelompok (Nurhayati dkk, 2019;Syafei, 2019;Selviani, 2019). Dalam penerapan model pembelajaran Problem Based Instruction pada mata pelajaran IPS materi kelangkaan dan kebutuhan manusia guru bisa mensimulasikan permasalahan kelangkaan sumber daya yang terbatas dihadapkan dengan kebutuhan manusia yang tidak terbatas sebagai konteks bagi siswa untuk mempelajari materi tersebut.…”
Section: Problem Based Instructionunclassified
“…Regarding this, the results of Prihatin's research (2020) and Wahyudi's research (2017) concluded that textbooks (which contain intolerant content) are one of the gateways for radicalism to enter educational institutions. On that basis, the development of teaching materials is one of the right steps to prevent radicalism among students and university students, as was done by Syafei (2019).…”
Section: Respondents' Perceptions Of Islamic Education Lecture Teachi...mentioning
confidence: 99%
“…Dalam materi ini peserta didik dituntut untuk memahami makna beriman kepada Rasul, bagaimana cara mengimaninya, apa saja sifat yang melekat sifat sifat yang ada pada nabi dan Rasul serta dapat memberikan contoh dalam kehidupan sehari-hari mereka, pengembangan bahan ajar perlu disesuaikan dengan model pembelajaran seperti Problem Based Learning dalam pembelajaran agama Islam (Syafei, 2019). Namun, sebagaimana pengalaman selama bertugas di sini, dalam ketrampilan membaca teks latin dan memahami banyak dari anak kelas 4 yang belum terlalu lancar membaca apalagi memahami teks bacaanya.…”
Section: Pendahuluanunclassified